Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
[tex](x-5)-(x-1)=-4[/tex]
[tex]=2x-4[/tex]
[tex](x-5)+(x+1)=-6[/tex]
[tex](x-5)+(x-1)=2x-6[/tex]
Step-by-step explanation:
In each of the expressions we first need to open the brackets and change the sign according to the sign preceding the bracket. After that we perform simple arithmetic to find the result.
[tex](x-5)-(x-1)=x-5-x+1[/tex]
[tex]=-4[/tex]
[tex](x-5)+(x+1)=x-5+x+1[/tex]
[tex]=2x-4[/tex]
[tex](x-5)-(x+1)=x-5-x-1[/tex]
[tex]=-6[/tex]
[tex](x-5)+(x-1)=x-5+x-1[/tex]
[tex]=2x-6[/tex]
The answers are
[tex](x-5)-(x-1)=-4[/tex]
[tex](x-5)+(x+1)=2x-4[/tex]
[tex](x-5)+(x+1)=-6[/tex]
[tex](x-5)+(x-1)=2x-6[/tex]
Answer:
Step-by-step explanation:
I got it right on edge 2022!
![View image waterlemmon2009](https://us-static.z-dn.net/files/d8b/7fd85b3519d33bccaea31d3ec9c95f8c.jpg)
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.